POLITICAL PARTIES OF UZBEKISTAN ("Conference on Universal Science Research 2023", 2024)
The Republic of Uzbekistan, since gaining independence in 1991, has seen the development of a multi-party system that operates within the framework of a presidential republic. This abstract provides an overview of the political parties that shape the nation's governance and political discourse. The political arena of Uzbekistan is characterized by the presence of both ruling and opposition parties, each with its own ideologies, policies, and visions for the future of the country.The dominant party, the Liberal Democratic Party of Uzbekistan (UzLiDeP), supports market reforms and economic liberalization and holds a significant majority in the legislative chamber. Other notable parties include the Democratic Party of Uzbekistan "Milliy Tiklanish," advocating for national revival and cultural development, and the People's Democratic Party of Uzbekistan, which focuses on social welfare and represents the interests of the working class.